ANALYSIS OF KINEMATIC FOR LEGS OF A HEXAPOD USING DENAVIT-HARTENBERG CONVENTION - Luo Qingsheng; Julpri Andika (Universitas Mercu Buana, 2018)
The headway of manipulator robots makes the development of a hexapod quite fast. Unfortunately, a hexapod is unstable to moving in a regular movement with some values added to programming algorithms. Various techniques implemented yet to the algorithms, like entering the degree values of each servo. However, to simplify the implementation of the algorithms, need some equations. This paper offered a hexapod control system based on Arduino that using Denavit-Hartenberg parameters to produce the equations. Various experiments have performed. Based on the experiments the offered system able to simplify the programming algorithms.